Kualitas Produk dan Harga Terhadap Keputusan Pembelian dengan Purchase Intention Sebagai Variabel Intervening - Nur Sakinah; Fani Firmansyah (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2021)
This study aims to examine the effect of product quality and price on purchasing decisions through buying interest. This study uses a quantitative approach. The analytical model used in this study is path analysis using SPSS 16. The data used are primary data through questionnaires. Samples were taken as many as 100 respondents who were determined by purposive sampling technique. The results showed that Product Quality had an effect on Purchase Decisions with a significance of 0.016 0.05. Price has an effect on Purchase Decision with a significance value of 0.000 0.05. Buying Interest has an effect on Purchase Decision with a significance value of 0.002 0.05. This study also shows that Purchase Interest is able to be a mediating variable between Product Quality on Purchase Decisions and Price on Purchase Intention.